An evaluation of the coverage of theoretically based implementation factors in disseminated classroom physical activity programs. Issue 4 (26th December 2018) - Calvert, Hannah G; Lane, Hannah G; Bejarano, Carolina M; Snow, Kelli; Hoppe, Kate; Alfonsin, Nicole; Turner, Lindsey; Carlson, Jordan A
Abstract : Classroom physical activity programs identified through an internet search provided few materials and resources that included a wide array of factors for supporting ongoing and widespread implementation success. Abstract: Classroom-based physical activity (CBPA) is increasingly recommended as a method to support children's physical activity, health, and academic performance. Many adoption-ready programs exist to aid in the implementation of CBPA in schools; yet, implementation rates remain low. The purpose of this study was to evaluate the extent to which resources provided by adoption-ready CBPA programs addressed theory-based implementation contextual factors to support implementation. Existing CBPA programs ( N = 37) were identified through Internet searches and all materials (e.g., implementation guides) provided by each program were coded for their inclusion of 51 implementation factors based on the Consolidated Framework for Implementation Research (CFIR). Analyses were conducted to compare inclusion of implementation factors across CFIR Domains and by three program groupings: free (yes/no), research evidence (yes/no), and targeted to teacher only (vs. school). Programs covered a mean of 25.9 per cent ( SD = 18.7 per cent) of the 14 Inner Setting implementation factors, 34.2 per cent ( SD = 18.0 per cent) of the 6 Characteristics of Individuals implementation factors, and 34.8 per cent (SD = 24.3 per cent) of the 8 Process implementation factors. Programs with research evidence covered more implementation factors than programs without research evidence (43.7 vs. 25.9 per cent; p < .05). Although numerous adoption-ready CBPA programs are available and have many strengths, their inclusion of theory-based factors that support or inhibit implementation is generally low. Consideration of such factors, including organizational climate and teacher-level behavior change, is likely critical to supporting ongoing school-wide implementation of CBPA. Research is needed to develop and test effective strategies for addressing these factors to support more widespread CBPA implementation.